The relationship between child-parent relationship and child temperament - Pang, Adeline Zou Yun (2024)
It has long been noted that child-parent relationship has a significantly impact on the children’s growth and development. However, in Malaysia, it is often strained by limited parental involvement due to social and economic factors, such as parents working multiple jobs. This can negatively impact the quality of the parent-child bond. Despite these challenges, the effects of the parent-child relationship on child temperament remain understudied. To bridge the knowledge gap, this study examines how closeness and conflict in the parent-child relationship relate to child temperament, focusing on surgency, negative affect, and effortful control. Using Bronfenbrenner’s ecological systems theory and Bowlby’s attachment theory, the research adopts a quantitative correlational approach. Data were collected from 87 parents (48 fathers and 39 mothers) of 4- to 6-year-old children in Kajang through an online questionnaire, utilizing convenience sampling. Pearson correlation analysis was conducted to investigate these relationships. Findings revealed that closeness in the parent-child relationship was positively correlated with all dimensions of child temperament: surgency (r= 0.277, p<0.05), negative affect (r=0.454, p<0.05), and effortful control (r= 0.382, p<0.05). Conflict, however, was positively correlated only with negative affect (r=0.710, p<0.05) showing no significant association with surgency (r=0.183, p> 0.05) or effortful control (r=-0.16, p>0.05). These results emphasize the importance of parental awareness of their child’s temperament and its influence on behaviour. These finding emphasized importance of parents being aware of their children's temperament, and how it influences their behaviour. Also, this implied to the preschool principal and teachers to enhance strategies that support parental engagement and parenting skills. The study limitation included its reliance on quantitative methods and its limited representativeness due to the small sample size and convenience sampling. Future research should explore mixed methods, larger samples, and random sampling to better understand the link between the child-parent relationship and child temperament.